Butyrate induced Caco-2 cell apoptosis is mediated via the mitochondrial pathway. Issue 1 (1st January 2003) - Ruemmele, F M; Schwartz, S; Seidman, E G; Dionne, S; Levy, E; Lentze, M J
Abstract : Background: During the process of tumorigenesis most colon cancer cells acquire resistance to apoptosis. The short chain fatty acid butyrate is well established as an antitumour agent which selectively induces apoptosis in colon cancer cells but not in normal intestinal epithelial cells. Aims: To analyse the signalling pathway of butyrate induced apoptosis. Methods: Using Caco-2 cells we focused on the bcl family of proteins, mitochondrial pathway, and caspase signalling cascade involved in butyrate induced apoptosis. Techniques employed included western blots, immunofluorescence, as well as experiments with peptide inhibitors of specific caspases. Results: Butyrate induced a clear shift of the mitochondrial bcl rheostat towards a proapoptotic constellation, as demonstrated by upregulation of proapoptotic bak accompanied by reduced antiapoptotic bcl-xL levels. This was associated with translocation of cytochrome-c from the mitochondria to the cytosol, resulting in activation of the caspase cascade via caspase-9. Key executioner enzymes were caspases-3 and -1. No effect of butyrate on regulatory proteins of the inhibitor of apoptosis family was observed. Conclusions: Butyrate induced Caco-2 cell apoptosis via the mitochondrial pathway. Upregulation of bak and translocation of cytochrome-c were upstream of the caspase cascade. Subsequently, this cascade was activated via the formation of an apoptosome.